Disruptive gratification: A thought-provoking impulse to pacify the Ukraine war - Ingo Pies (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2022)
This short text suggests that Germany and the European Union should generously welcome not only war refugees from Ukraine, but also Russian soldiers who have deserted. As a disruptive gratification, this would be a humanitarian contribution to asymmetric warfare and would support Ukraine's existing measures with credibility and resources. – – Dieser Kurztext unterbreitet den Vorschlag, dass Deutschland und die Europäische Union nicht nur Kriegsflüchtlinge aus der Ukraine großzügig aufnehmen sollte , sondern auch russische Soldaten, die desertiert sind. Dies wäre - als disruptive Belohnung - ein humanitärer Beitrag zur asymmetrischen Kriegsführung und würde bereits bestehende Maßnahmen der Ukraine mit Glaubwürdigkeit und Ressourcen unterstützen.
Keywords: 330; ordonomics; business ethics; Ukraine war; disruptive gratification; Ordonomik; Wirtschaftsethik; Ukrainekrieg; Disruptive Belohnung